Implementing Green Economy Concepts to Realise IKN's Vision as a Green City - Amirullah, Muhammad Yani; Maksudi, E. Imam (Lembaga Ketahanan Nasional Republik Indonesia, 2024)
Purpose: To analyse the challenges and strategies for implementing the green economy concept in the development of Indonesia’s new capital (IKN) in East Kalimantan, focusing on environmental, social, and economic risks while formulating policy recommendations to support IKN's vision as a Green City. Design/Methodology/Approach: A qualitative approach is applied, combining policy analysis and literature reviews from academic publications, journals, regulations, and government reports on sustainable development. The descriptive-critical method evaluates the implementation of green economy policies. Findings: IKN’s development faces critical challenges, including environmental degradation, social inequality, limited green infrastructure, and economic dependence on extractive industries. Key strategies include enhancing stakeholder coordination, optimising green incentive policies, and leveraging sustainable technologies. Originality/Value: Provides fresh insights into the importance of a green economy approach in new urban development. Data-driven policy recommendations are offered to guide the government and stakeholders in designing sustainable development strategies for IKN